Wildlife Is a Potential Source of Human Infections of Enterocytozoon bieneusi and Giardia duodenalis in Southeastern China - Zhang, Yan; Mi, Rongsheng; Yang, Lijuan; Gong, Haiyan; Xu, Chunzhong; Feng, Yongqi; Chen, Xinsheng; Huang, Yan; Han, Xiangan; Chen, Zhaoguo (Frontiers in Microbiology, 2021)
Wildlife is known to be a source of high-impact pathogens affecting people. However, the distribution, genetic diversity, and zoonotic potential of Cryptosporidium, Enterocytozoon bieneusi, and Giardia duodenalis in wildlife are poorly understood. Here, we conducted the first molecular epidemiological investigation of these three pathogens in wildlife in Zhejiang and Shanghai, China. Genomic DNAs were derived from 182 individual fecal samples from wildlife and then subjected to a nested polymerase chain reaction–based sequencing approach for detection and characterization. Altogether, 3 (1.6%), 21 (11.5%), and 48 (26.4%) specimens tested positive for Cryptosporidium species, E. bieneusi, and G. duodenalis, respectively. Sequence analyses revealed five known (BEB6, D, MJ13, SC02, and type IV) and two novel (designated SH_ch1 and SH_deer1) genotypes of E. bieneusi. Phylogenetically, novel E. bieneusi genotype SH_deer1 fell into group 6, and the other genotypes were assigned to group 1 with zoonotic potential. Three novel Cryptosporidium genotypes (Cryptosporidium avian genotype V-like and C. galli-like 1 and 2) were identified, C. galli-like 1 and 2 formed a clade that was distinct from Cryptosporidium species. The genetic distinctiveness of these two novel genotypes suggests that they represent a new species of Cryptosporidium. Zoonotic assemblage A (n = 36) and host-adapted assemblages C (n = 1) and E (n = 7) of G. duodenalis were characterized. The overall results suggest that wildlife act as host reservoirs carrying zoonotic E. bieneusi and G. duodenalis, potentially enabling transmission from wildlife to humans and other animals.